Working with multiple representations: preservice teachers' decision-making to produce a digital explanation. (2nd January 2020) - Nielsen, Wendy; Turney, Annette; Georgiou, Helen; Jones, Pauline
ABSTRACT: A "digital explanation" is a science learning task where learners explain science content to non-expert others, in this case, the learners are primary preservice teachers [PST] in a science methods class. In the task, PST are assigned a prompt based on science content from the New South Wales K-6 syllabus and generate or source multiple representations to design and produce this stand-alone digital artefact. In this study, PST were interviewed about their decision making in producing the digital explanation, which offers insight into the design process and what makes for a successful product. Data include the digital explanations, interviews with nine PST, marking rubrics and rationale statements generated as part of the task. Thematic coding shows PST make design decisions for four principal reasons: content, engagement, clarity and unconscious selection. Decisions around content and engagement prevail and their decisions reveal keys to success in creating a digital explanation. We also note a tension between emphasis on engagement over content, which may reflect that the intended audience is young children and PST have a strong desire to gain and keep children's interest.